Identify hazardous situations to work more productively - Huki Chandra; Perdana Suteja Putera; Yohanes Setiawan (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
In carrying out social activities, identifying potential hazards is important to achieve safety, health, and welfare. Recognizing and identifying hazards is one of the efforts that need to be made to work more productively. In addition, by recognizing and identifying hazards we can know about hazardous situations that may not have been predicted. Therefore, recognizing and identifying hazards needs to be done by every individual. Based on these problems, awareness of the importance of occupational safety and health is needed. This awareness can be increased through knowledge of the types of hazards in the surrounding environment. Therefore, there is a need for training on the types of hazards needed to identify hazards. Identifying hazards needs to be done to determine appropriate risk controls. Training activities to recognize hazards in the surrounding environment have been effective in increasing the level of understanding of participants. The results of the participants' safety awareness test were tested using the wilcoxon signed the rank test method to see whether there was a difference in the level of safety awareness before and after the education. This statement is proven by the significant increase in participants' final test scores compared to their initial test scores so that this training activity on recognizing hazards in the surrounding environment can be carried out again at another time. This training activity on recognizing hazards in the surrounding environment was deemed satisfactory for the training participants and quite important with a mean of 4.66 on a scale of 5.00, so it can be concluded that this training activity has satisfied the participants and has adequately answered the hopes and interests of the training participants